Documentación del proceso de mantenimiento según la NTC ISO 9001:2015 en una empresa de servicios tecnológicos (2019)
The objective of this work is to determine the documented information on the maintenance process at Bfocus Technologies S.A.S. The documented information was structured based on the requirements established in the NTC ISO 9001: 2015 standard, as well as the internal processes and the company's own needs. Initially, a process map is established in order to graphically express the interaction between the processes that intervene in the organization, identifying the inputs and outputs, and classifying them into three general types: operational, support and management. Subsequently, the characterization of the maintenance process was carried out, identifying the inputs and outputs, activities, as well as the resources and information required or coming from other processes.